P1-S6.37 Can rapid syphilis tests be implemented and improve screening for maternal syphilis in a third level hospital?. (10th July 2011) - La Rosa Roca, S; Garcia, P
Abstract : Background: Syphilis continues to be one of the most important causes of maternal and child morbi-mortality, frequently being more common than HIV. Ideal diagnostic test should provide rapid and accurate results to provide timely diagnosis and treatment. Rapid syphilis testing is an excellent option. The objective of this study is to determine the feasibility of the implementation of Rapid Syphilis Testing (RST, Syphilis 3.0 BioLine) and the impact on maternal screening for syphilis at a third level hospital in Peru: the National Maternal and Perinatal Institute (INMP). Methods: Between February and December of 2010, RST was implemented in the Antenatal care (ANC), labour and miscarriage services. The National guidelines recommended screening for syphilis in all those services with RPR. Health workers (midwives, nurses and laboratory technicians, depending on the service) were properly trained on the use of RST and their performance was monitored throughout the study. Results: RST was performed on 15 116 women, with a prevalence of syphilis (RPR reactive, TPPA positive) of 1% for ANC, 0.7% for miscarriage services and 0.8% at labour. The coverage of screening for syphilis improved from 82% with RPR to 99% with RST at the ANC services; from 0% to 91% at the miscarriage services and from 79% to 94% at labour. At baseline, at the ANC visit, the results of the RPR were only available 15 days after the visit, resulting in a low coverage for treatment when the test was positive, 39%. With the implementation of the RST, the results and treatment were given immediately at the same visit, resulting on treatment coverage of 95%. The RST was very well accepted by the providers and patients. Conclusions: This study shows the feasibility, acceptability and improvements on screening associated to the implementation of RST in a third level hospital. In addition of improving coverage and treatment, our results triggered changes in the institutional policies for syphilis control.